The Development of Local Government Empowerment Model to Support Kredit Usaha Rakyat s Program (KUR) for Poverty Alleviation - Rifai, Bachtiar (Jurnal Kajian Ekonomi dan Keuangan, 2013)
Indonesian government has been launched poverty alleviation framework which consists of Four Clusters such as: Direct Transfer (BLT'); National Program for Community Empowerment (PNPMJ; Kredit Usaha Rakyat (KUR); and energy, housing, transportation for poor. Unfortunately, KUR hasn't reached poor and reduce the poverty significantly. It is predicted that Local Government hasn't involved structurally and formally in KUR’s implementation. The study is developed from primary and secondary data which has been conducted since 2012 in Five Provinces (Central Java, East Java, Bengkulu, Yogyakarta and Mataram). Primary data were generated by three instruments such as questionnaire (600 units which was divided into two group- KUR and non KUR), in depth interview for key persons and Focus Group Discussion which was representing stakeholder. The result shows that the roles of Local Government in KUR implementation are still limited. It can be identified as follows: being administrator for Communication for KUR, socialization in SMEs, and facilitating for KUR assistant for SMEs. One of obstacles is Local Government hasn't engaged yet on KUR syndications.